2013
DOI: 10.1039/c2cs35239g
|View full text |Cite
|
Sign up to set email alerts
|

Coordination chemistry beyond Werner: interplay between hydrogen bonding and coordination

Abstract: A tutorial review is presented dealing with the role of hydrogen bonding in coordination compounds. Examples are given for important intramolecular hydrogen bonding, and stabilising unusual coordination geometries, or reactive species. Also examples are discussed for intermolecular H-bonds between coordination entities and anions, and for stabilising crystal lattices, like in coordination polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 83 publications
2
40
0
Order By: Relevance
“…There are different factors responsible for an arrangement of molecules and ions in crystal structures. [1][2][3][4] However, it is commonly accepted that the hydrogen bonds are among the most important interactions influencing such arrangement owing to their properties, mainly their strength and directionality. [5][6][7][8][9][10] Furthermore, the hydrogen bond plays a key role in numerous chemical, physical, and biological processes, thus it is analyzed very often in the gas phase, liquid and solid, both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different factors responsible for an arrangement of molecules and ions in crystal structures. [1][2][3][4] However, it is commonly accepted that the hydrogen bonds are among the most important interactions influencing such arrangement owing to their properties, mainly their strength and directionality. [5][6][7][8][9][10] Furthermore, the hydrogen bond plays a key role in numerous chemical, physical, and biological processes, thus it is analyzed very often in the gas phase, liquid and solid, both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…The atom A is usually carbon but other bonds such as for example Si À X [24] or Sb À X [32] have been also considered. The same halogen X atom that possesses the region of the positive electrostatic potential is surrounded by the Abstract: Ab initio calculations were performed on complexes of ZH 4 + (Z = N, P, As) and their fluoro derivatives, ZFH 3 + and ZF 4 + , with a HCN (or LiCN) molecule acting as the Lewis base through the nitrogen electronegative center. It was found that the complexes are linked by the Z À H···N hydrogen bond or another type of noncovalent interaction in which the tetravalent heavy atom of the cation acts as the Lewis acid center, that is, when the Z···N link exists, which may be classified as the s-hole bond.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen-bonding interactions can have important effects on the properties of coordination compounds [125]. The X-ray molecular structures of trans-[RuCl 2 (cyclam)]Br and trans-[RuCl(4-acpy)(cyclam)](BF 4 ) show significant Cl-H(N cyclam ) bond interactions (Table 3).…”
Section: X-ray Diffractionmentioning
confidence: 98%
“…When such cis and trans forms are seen in bipyrazole coordination compounds hydrogen bonds have been identified to play an important role via the so‐called second sphere coordination to lock the conformers into place and to localize the NH group through these supramolecular assemblies . Referring to this concept, the anionic ring around the central metal atom seen in metal‐pyrazole‐coordination compounds was regarded as a possible strategy to observe the neutral, NH group versions of H 2 azbpz in a supramolecular matrix , , , .…”
Section: Introductionmentioning
confidence: 99%